2022
DOI: 10.1088/1674-1137/ac3071
|View full text |Cite
|
Sign up to set email alerts
|

Revealing pion and kaon structure via generalised parton distributions *

Abstract: Clear windows onto emergent hadron mass (EHM) and modulations thereof by Higgs boson interactions are provided by observable measures of pion and kaon structure, many of which are accessible via generalised parton distributions (GPDs). Beginning with algebraic GPD Ansätze, constrained entirely by hadron-scale and K valence-parton distribution functions (DFs), in whose forms both EHM and Higgs boson influences are manifest, numerous illustrat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 94 publications
3
40
0
Order By: Relevance
“…We implement evolution by using the all-orders scheme introduced elsewhere [53][54][55] and elucidated in Refs. [75][76][77]. Our practical implementation is based on the process-independent effective charge, α(k 2 ), described in Refs.…”
mentioning
confidence: 99%
“…We implement evolution by using the all-orders scheme introduced elsewhere [53][54][55] and elucidated in Refs. [75][76][77]. Our practical implementation is based on the process-independent effective charge, α(k 2 ), described in Refs.…”
mentioning
confidence: 99%
“…( 23) -modern calculations of groundstate pseudoscalar-meson LFWFs, e.g., Refs. [40,85,88,[100][101][102][103][104][105][106] do not exhibit features that could produce wiggles in the associated valence-quark DFs. Con- sequently, we hereafter represent Eqs.…”
Section: Threshold Resummation Using Mellin-fourier Methodsmentioning
confidence: 96%
“…Comparisons with such calculations [86,[88][89][90] and also data [91][92][93] show that SCI results are typically a reliable guide for long-wavelength properties of hadrons, such as masses and decay constants, but, unsurprisingly, fail in applications that are sensitive to and/or reveal structural properties. The hadron-scale DF in Eq.…”
Section: Content Of Drell-yan Datamentioning
confidence: 99%
“…It has been demonstrated with the pseudoscalar mesons [10,36,37] and then generalized to the case of vector mesons [38]. Based on the dynamically solved BS wave functions, which accumulated lots of success in hadron study within the Dyson-Schwinger equations (DSEs) formalism [39][40][41][42][43][44][45], the parton distribution amplitude [46][47][48], generalized parton distributions (GPDs) and TMDs of pseudoscalar mesons [49,50] are further studied. Exclusive process is also studied, e.g., without introducing any new parameters, the 𝜌 and 𝐽 /𝜓 LF-LFWFs are put into the color dipole model study of diffractive vector meson productions in e-p collison, and agreement is found with data from HERA [38].…”
Section: Introductionmentioning
confidence: 99%